2020
DOI: 10.3390/en13010206
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study to Investigate the Effects of Operational Conditions on Methylcyclohexane Dehydrogenation for Hydrogen Production

Abstract: In the recent era, hydrogen has gained immense consideration as a clean-energy carrier. Its storage is, however, still the main hurdle in the implementation of a hydrogen-based clean economy. Liquid organic hydrogen carriers (LOHCs) are a potential option for hydrogen storage in ambient conditions, and can contribute to the clean-fuel concept in the future. In the present work, a parametric and simulation study was carried out for the storage and release of hydrogen for the methylcyclohexane toluene system. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A number of substances have been proposed as LOHCs. Prominent examples are toluene and N‐ethyl carbazole . Yet, these carriers come with a number of unfavorable properties.…”
Section: Introductionmentioning
confidence: 99%
“…A number of substances have been proposed as LOHCs. Prominent examples are toluene and N‐ethyl carbazole . Yet, these carriers come with a number of unfavorable properties.…”
Section: Introductionmentioning
confidence: 99%
“…For the cost estimation, the following important parameters are considered: (1) catalyst cost, (2) operational expenses, (3) electricity cost, (4) depreciation cost, and (5) substation of LOHC material [5,6]. The analysis shows that liquid organic hydrogen carriers (LOHC) are the most suitable option for the storage and release of hydrogen since the energy demand and cost required for the LOHC system is the lowest, followed by compressed hydrogen storage, and liquid hydrogen storage [7].…”
Section: Fuelmentioning
confidence: 99%
“…There are several problems associated with the naphthalene-decalin system, which makes this system unfavorable for the operation, (1) the solid nature of naphthalene which causes difficulties in transportation and storage, and (2) high energy requirement for the dehydrogenation. In comparison to these three systems, the perhydro-dibenzyl-toluene and dibenzyltoluene (PDBT-DBT) system provides several advantages: (1) none of the components is carcinogenic, (2) liquid nature, therefore no handling, storage, and transportation issues, (3) lower vapor pressure of DBT allow easy release of hydrogen in the liquid phase, low vapor pressure is advantageous with respect to the safety and storage of PDBT-DBT, low vapor pressure means that these compounds can be stored at atmospheric conditions and when needed, these can be dehydrogenated via reaction, (4) lower volatility helps in obtaining comparatively higher purities of hydrogen, and (5) higher value of volumetric density [7,[10][11][12][13][14]. Regarding the high energy requirements of dehydrogenation in this system, it has been reported that the process can be performed efficiently by using a microstructured reactor [14,15].…”
Section: Naphthalene-decalin Systemmentioning
confidence: 99%
“…Meanwhile, iterative catalytic hydrogenation/dehydrogenation of arenes/corresponding naphthalene pairs has been used for hydrogen storage and transportation [3]. To convert stable molecules under mild conditions (for example, below 100 • C) with high selectivity and yield, noble metals such as platinum, ruthenium and rhodium are required as the main catalytic components in these processes [4][5][6][7][8][9][10][11][12][13]. Nevertheless, these catalysts have not received widespread industrial use because of their high cost, complex preparation procedures and vulnerability to sulfur poisoning [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, catalytic performance of a given catalyst could be improved by doping transition metals, and noble metals are widely used as key additives to promote the catalytic performance of carbide catalysts [41], which inevitably increases the cost of the catalysts and consequently hinders their industrial applications [3,4,30,31,33,42,43]. It is of great industrial and academic interest to use inexpensive additives and develop preparation methods to achieve cheap and highly active catalysts.…”
Section: Introductionmentioning
confidence: 99%